TEORI-TEORI BELAJAR DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA - Ahmad, Idrus; Djais, Idwan (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
Learning theories are considered to have opened the veil on language learning, both first and second languages. The learning theories that are the object of this study are the Nativism theory pioneered by Noam Chomsky, the Behaviorism theory pioneered by John B. Watson, the Cognitivism theory, and the Constructivism theory pioneered by Jean Piaget, which are very influential in language learning. Two controversial theoretical views from America, namely the theory of nativism and behaviorism. Nativism theory argues that language mastery is natural. Meanwhile, behaviorism theory argues that language mastery is